Optimizing the Flow of Inpatient Acceptance at the Internal Medicine Clinic of Stone Baptist Hospital - Lidia Emilinda; Dolly Irbantoro; Tita Hariyanti (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
The waiting time for hospitalization in internal medicine clinics at Baptis Batu Hospital has not yet reached the minimum service standard indicator. Batu Baptis Hospital determines the standard inpatient waiting time <120 minutes starting from the patient being decided on hospitalization until the patient enters the care room and infusion installation by the nurse. Reducing the factors that affect the length of time waiting for hospitalization in internal medicine clinics. This study was qualitative with unstructured interviews, FGDs, and observations with 3 participants. Primary data were obtained from time motion study observations and secondary data were obtained from the minimum service standard report (SPM) of Baptis Hospital Batu. The main factor of the length of time waiting for inpatient in internal medicine clinics was the absence of special officers in the action room and the role of inter-unit officers did not communicate well to optimize inpatient waiting time. The flow process for inpatient admissions exceeds the standard causing a long waiting time for inpatients. Suggestion from this research is the addition of admission units in outpatient installations to reduce the waiting time.